A Reflection of EHPS 2025 as an Online Attendee - Leona Ryan (European Health Psychologist, 2026)
I entered the 39th Annual EHPS Conference as a reluctant virtual attendee, navigating the Zoom fatigue common to post pandemic academia. This article reflects on how that experience shifted my perception of digital integration. I explore how the conference infrastructure moved me from a passive observer to an integrated member of the scientific community, facilitating a sense of presence often missing in online formats. Drawing on parallels with my own research into virtual human simulations, I discuss the necessity of reciprocal interaction in digital spaces. This reflection highlights how high quality hybrid models address the real world tensions within academia of personal commitments, financial constraints, and environmental sustainability. In conclusion, I suggest that inclusive digital access to our conferences must becomethe baseline standard for a more equitable and sustainable professional community.